Simulated trawling: Exhaustive swimming followed by extreme crowding as contributing reasons to variable fillet quality in trawl-caught Atlantic cod (Gadus morhua) - Svalheim, Ragnhild Aven; Aas-Hansen, Øyvind; Heia, Karsten; Karlsson-Drangsholt, Anders; Olsen, Stein Harris; Johnsen, Helge K. (PLOS ONE, 2020)
Trawl-caught Atlantic cod (Gadus morhua) often yield highly variable fillet quality that may be related to capture stress. To investigate mechanisms involved in causing variable quality, commercial-sized (3.5±0.9 kg) Atlantic cod were swum to exhaustion in a large swim tunnel and subsequently exposed to extreme crowding (736±50 kg m -3 ) for 0, 1 or 3 hours in an experimental cod-end. The fish were then recuperated for 0, 3 or 6 hours in a net pen prior to slaughter to assess the possibility to reverse the reduced fillet quality. We found that exhaustive swimming and crowding were associated with increased metabolic stress, as indicated by increased plasma cortisol, blood lactate and blood haematocrit levels, accompanied by reduced quality of the fillets due to increased visual redness and lower initial muscle pH. The observed negative effects of exhaustive swimming and crowding were only to a small degree reversed within 6 hours of recuperation. The results from this study suggest that exhaustive swimming followed by extreme crowding can reduce fillet quality, as measured by fillet redness and muscle pH, and contribute to the variable fillet quality seen in trawl-caught Atlantic cod. Recuperation for more than six hours may be required to reverse these effects.